The Trauma Of Conformity: Identity Struggles In Dead Poets Society - Nisa, Zahrotun (Litteratura: Jurnal Bahasa dan Sastra, 2025)
This study examines psychological trauma caused by social conformity pressures experienced by Neil Perry in the film Dead Poets Society (1989). Using a qualitative film analysis approach grounded in Cathy Caruth’s Trauma Theory, the research analyzes selected scenes and dialogues to explore how trauma emerges, repeats, and remains unprocessed within the character’s identity formation. The data consist of purposively selected scenes and dialogues that depict parental authority, institutional discipline, and moments of self-assertion. The findings reveal that conformity pressures from family and educational institutions produce unresolved trauma manifested through silence, obedience, dissociation, and ultimately suicidal ideation. This study contributes to film trauma studies by demonstrating how Caruth’s concept of belatedness and unclaimed experience explains adolescent identity crises in cinematic narratives.